Should We Prefer Magnetic Resonance Imaging to Physical Examination in Meniscal Tears - Arıcan, Gökhun; Özmeriç, Ahmet; Şahin, Özgür; İltar, Serkan; Alemdaroğlu, Kadir Bahadır (The Journal of Knee Surgery, 2019)
The aim of this study was to compare the sensitivity, specificity, accuracy, positive and negative predictive values of magnetic resonance imaging (MRI), and clinical examination in the diagnosis of meniscus tears with the findings obtained from the knee joint arthroscopy. A retrospective study was made of 452 patients who underwent knee arthroscopy due to meniscus tears between 2012 and 2017. Physical examination was performed using the Thessaly's, McMurray's, and Joint line tenderness tests (JLTT). On preoperative MRI, medial meniscal tears were observed in 292 patients, lateral meniscal tears in 96 patients, and medial and lateral meniscal tears in 64 patients. According to the arthroscopy results, 284 patients had medial meniscal tears, 108 patients had lateral meniscal tears, and 60 patients had medial and lateral meniscal tears. Sensitivity and specificity of the JLTT was determined as 93 and 86% respectively for medial meniscal tears and 94 and 89% for lateral meniscal tears. The McMurray's test was 60% sensitive, 68% specific for medial meniscal tears (MMT), and 73% sensitive and 68% specific for lateral meniscus tears (LMT). The Thessaly's test was 93% sensitive and 87% specific for medial meniscal tears; and 94% sensitive and 88% specific for LMT. Compared with the arthroscopic findings, MRI was observed to have sensitivity of 94% for MMT and 84% for LMT. For specificity, the values were 89% for MMT and 91% for LMT. Accuracy was 89% for MMT and 86% for LMT. In comparison with the arthroscopic findings, the triple test was determined to have sensitivity of 92% for MMT and 89% for LMT. The specificity was 88% for MMT and 91% for LMT. The results of this study showed that a combination of selected physical examination methods is as sensitive as MRI in the diagnosis of meniscus tears.
Keywords: meniscal tears; McMurray's test; JLTT; Thessaly's test